Evaluating the decolonisation of the Humanities curriculum at the University of Cape Town: Khanyisa courses as a case study - Phetlhu, Ontiretse (School of Education, 2025)
This study sought to bring the conversation around the decolonisation of the curriculum to the fore by evaluating the decolonial work that the Humanities Faculty at the University of Cape Town has attempted to do with regard to the undergraduate degree programme through the introduction of a new suite of course, called the Khanyisa Courses. As such, this study establishes the various ways in which the Humanities faculty through the Khanyisa Courses (specifically the course called: Literature: How and why? – ELL1013F) has attempted to decolonise the curriculum in terms of the way the course is structured, the way it is taught and the way the course is assessed. The aim is to establish whether the course fulfils the decolonial project by means of disrupting and challenging the Eurocentric traditions of teaching and assessing the course. The thesis argues that the ELL1013F course does decolonial work in that it adopts a paradigm shift away from Eurocentric traditions within the discipline of literary studies. The course does this decolonial work by means of adopting epistemic disobedience as one of the approaches in how the course is structured and how the content is taught and assessed – with the idea of the students' positionality being at the at the centre of the learning process thereby disrupting existing hierarchies of knowledge. Furthermore, the thesis argues that the various modules also adopt different approaches in terms of Jansen's (2017) six conceptions of decolonisation and this varied from the different lecturers that taught the modules of the ELL1013F course. Lastly, this thesis shows how the course did not managed to fully decolonise the curriculum, at the level of assessment as it did not overtly disrupt hierarchies of western knowledge in any significant way.